1972
DOI: 10.1002/jhet.5570090639
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of the heterocyclic ring substituted 2′‐nitrobenzylphthalazine‐1,4‐diones

Abstract: We have synthesized and spectrally characterized the five possible heterocyclic ring substituted 2'-nitrobenzylphthalazine-l,4-diones. Selective alkylation of the tautomers of phthalazine-l,4-dione (phthalhydrazide) with 2'nitrobenzyl chloride furnishes the 0and N-monoalkyl isomers and the 0 , N -, 0,Oand N,N-dialkyl isomers.These isomers are depicted below along with the parent compound phthalazine-l,4dione (I) and the N-aminophthalimide derivative (VII), which is isomeric to the monoalkylated compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The above analysis of the 1 H-NMR and IR spectra indicated that under the applied reaction conditions quinazolidin-4( 3H )-one ( 7 ) undergoes N-substitution. Application of the same reaction conditions to alkylation of 2-phenyl-2,3-dihydrophthalazine-1,4-dione ( 8 ) and 1-phenyl-1,2-dihydropyridazine-3,6-dione ( 9 ) results in formation of the N-substituted derivatives 16 - 19 and 20 - 23 respectively, in agreement with both our own and literature reports on the structural determination of substituted lactams [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Resultssupporting
confidence: 89%
“…The above analysis of the 1 H-NMR and IR spectra indicated that under the applied reaction conditions quinazolidin-4( 3H )-one ( 7 ) undergoes N-substitution. Application of the same reaction conditions to alkylation of 2-phenyl-2,3-dihydrophthalazine-1,4-dione ( 8 ) and 1-phenyl-1,2-dihydropyridazine-3,6-dione ( 9 ) results in formation of the N-substituted derivatives 16 - 19 and 20 - 23 respectively, in agreement with both our own and literature reports on the structural determination of substituted lactams [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Resultssupporting
confidence: 89%
“…The position of the equilibrium depends not only on the type of amide, but also to a large extent on solvent [17][18][19][20]. The position of the equilibrium depends not only on the type of amide, but also to a large extent on solvent [17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…The position of the equilibrium depends not only on the type of amide, but also to a large extent on solvent [17][18][19][20].…”
Section: Synthesesmentioning
confidence: 99%